Paediatric tuberculosis in Singapore: a retrospective review - Sin Wee Loh; Koh Cheng Thoon; Natalie Woon Hui Tan; Jiahui Li; Chia Yin Chong (BMJ Publishing Group, 2018)
Background Tuberculosis (TB) is a major cause of mortality and morbidity in the world. Each case represents ongoing transmission and has a significant public health burden. We aim to examine the clinical profile of paediatric TB and compare pulmonary TB (PTB) with extrapulmonary TB (EPTB) in Singapore.Methods A retrospective study of patients admitted to KK Women's and Children's Hospital, Singapore from January 2008 to September 2017 with active TB was undertaken. The clinical characteristics and outcomes of patients with PTB and EPTB were compared.Results Seventy-five patients were diagnosed as having active TB (49 (65%) with PTB and 26 (35%) with EPTB). Patients with EPTB were more likely than those with PTB to be younger (median age 5.1 (IQR 1.2-10.2) years vs 10.1 (IQR 3.5-13.5) years), immunodeficient (35% vs 6%), with a lower haemoglobin count (median 11.2 (IQR 10.2-11.9) g/dL vs 12.0 (IQR 10.5-13.9) g/dL), lower recovery rate (27% vs 57%) and required longer duration of treatment (median 12 (IQR 9-12) months vs 6 (IQR 6-9) months). Common clinical presentations of both PTB and EPTB were significant fever (27%), cough (33%) and weight loss (32%). Overall mortality was 8% with septic shock responsible for three of the six deaths.Conclusion EPTB is more common in the younger age group and is associated with a lower recovery rate.